The use of preformed nanoparticles in the production of heterogeneous catalysts - Hondow, N.; Fuller, Rebecca (Academic Press, 2014)
Preformed iron oxide nanoparticles have been successfully assembled onto alumina and MCM-41 support materials. The particles are found to disperse evenly over the surface of the silicate; however, in the case of the alumina we find that in addition to areas of even distribution there is also some clustering of the particles. The materials are stable under heat treatment, with no signs of further aggregation during calcination. We investigate the reducibility of the materials through H 2 -TPR studies and we find that the particles are reducible around 500-550°C. The reduction process is complete at temperatures where MCM-41 can undergo degradation, supporting that the alumina based materials are more suited to the multiple base oxidation reduction steps in the catalytic cycle. © 2013 Elsevier Inc.